(untitled) (International Conference on Education, Psychology and Humanities, 2026)
Albert Camus is one of the prominent representatives of world literature of the 20th century, and is considered one of the creators who took an important place in French philosophy and literature. This article describes the character of a person who is indifferent to his fate, his emotions, and the behavior of a person who is indifferent to the values of society through the image of Marcel Meursault, the main character of Albert Camus’ story “The Stranger”. In this work, the author describes existentialism and absurdist literature by researching the role and difficulties of man in modern society.